Cannabis use assessment and its impact on pain in rheumatologic diseases: a systematic review and meta-analysis. (7th November 2020) - Guillouard, M; Authier, N; Pereira, B; Soubrier, M; Mathieu, S
Abstract: Objectives: Despite classic analgesic or effective treatments in rheumatic diseases, such as synthetic DMARDs in RA, patients remain in pain and often turn to non-prescribed pharmacological alternatives, such as cannabis self-therapeutic use. However, this medical use of cannabis has not been thoroughly studied. Methods: We performed a systematic literature review up to June 2020. The incidence of cannabis consumption was calculated by metaproportion. Differences between cannabis users and non-users were expressed as standardized mean differences using the inverse-variance method. We also assessed the effects of cannabis on pain. Results: A total of 2900 patients reported cannabis consumption in a sample of 10 873 patients [incidence 40.4% (95% confidence interval (CI): 0.28, 0.54)], and 15.3% (95% CI: 0.07, 0.27) specified that they were currently taking cannabis. Cannabis use was higher in the four fibromyalgia studies [68.2% (95% CI: 0.41, 0.90), n = 611] compared with seven articles concerning RA or lupus [26.0% (95% CI: 0.14, 0.41), n = 8168]. Cannabis consumption was associated with a decrease in pain intensity [VAS pain at baseline 8.2 (2.9) vs 5.6 (3.5) mm over time; pooled effect size −1.75 (95% CI: −2.75, −0.76)]. Cannabis users were younger [58.4 (11.4) vs 63.6 (12.1) years; P <0.001], more often smokers [OR 2.91 (95% CI: 1.84, 4.60)] or unemployed [OR 2.40 (95% CI: 1.31, 4.40)], and had higher pain intensity [5.0 (2.4) vs 4.1(2.6) mm; P <0.001] than non-users. Conclusion: Nearly 20% of patients suffering from rheumatologic diseases actively consume cannabis, with an improvement in pain. The issue of cannabis use in the management of these patients should be addressed during medical consultation, essentially with cannabis-based standardized pharmaceutical products.